Examining the course of transitions from hospital to home-based palliative care: A mixed methods study. (September 2021) - Saunders, Stephanie; Weiss, Marianne E; Meaney, Chris; Killackey, Tieghan; Varenbut, Jaymie; Lovrics, Emily; Ernecoff, Natalie; Hsu, Amy T; Stern, Maya; Mahtani, Ramona; Wentlandt, Kirsten; Isenberg, Sarina R
Background: Hospital-to-home transitions in palliative care are fraught with challenges. To assess transitions researchers have used patient reported outcome measures and qualitative data to give unique insights into a phenomenon. Few measures examine care setting transitions in palliative care, yet domains identified in other populations are likely relevant for patients receiving palliative care. Aim: Gain insight into how patients experience three domains, discharge readiness, transition quality, and discharge-coping, during hospital-to-home transitions. Design: Longitudinal, convergent parallel mixed methods study design with two data collection visits: in-hospital before and 3–4 weeks after discharge. Participants completed scales assessing discharge readiness, transition quality, and post discharge-coping. A qualitative interview was conducted at both visits. Data were analyzed separately and integrated using a merged transformative methodology, allowing us to compare and contrast the data. Setting and participants: Study was set in two tertiary hospitals in Toronto, Canada. Adult inpatients ( n  = 25) and their caregivers ( n  = 14) were eligible if they received a palliative care consultation and transitioned to home-based palliative care. Results: Results were organized aligning with the scales; finding low discharge readiness (5.8; IQR: 1.9), moderate transition quality (66.7; IQR: 33.33), and poor discharge-coping (5.0; IQR: 2.6), respectively. Positive transitions involved feeling well supported, managing medications, feeling well, and having healthcare needs met. Challenges in transitions were feeling unwell, confusion over medications, unclear healthcare responsibilities, and emotional distress. Conclusions: We identified aspects of these three domains that may be targeted to improve transitions through intervention development. Identified discrepancies between the data types should be considered for future research exploration.